An Interpolation Problem in the Class R[a,b] - Dyukarev, Yu. M.; Choque, Rivero A. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider an interpolation problem for matrix functions of the class R[a,b]. In the nondegenerate case, we describe all solutions in terms of fractional linear transformations. An explicit formula for the resolvent matrix is obtained.